THU0423 Epidemiology and survival of systemic sclerosis-systemic lupus erythematosus overlap syndrome. (12th June 2018) - Alharbi, S.; Ahmad, Z.; Bookman, A.; Touma, Z.; Sanchez-Guerrero, J.; Mitsakakis, N.; Johnson, S.R.
Abstract : Background: Systemic sclerosis (SSc) is an immune disorder characterised by vasculopathy and fibrosis that may overlap with another disease such as systemic lupus erythematous (SLE). Little is known about the epidemiology, clinical characteristics, and survival of SSc-SLE overlap (also called lupoderma). We evaluated the prevalence of SSc-SLE overlap syndrome, differences in SSc clinical characteristics and survival compared with SSc without SLE. Methods: A cohort study was conducted including subjects who fulfilled the ACR-EULAR classification criteria for SSc and/or the ACR criteria for SLE. The primary outcome was the time from diagnosis to death from all causes. Survival was evaluated using Kaplan Meier curves and Cox Proportional Hazard models. Results: We identified 1252 subjects (SSc n=1166, SSc-SLE n=86) with a SSc-SLE prevalence of 6.8%. SSc-SLE were younger at diagnosis (37.9 years versus 47.9 years, p<0.001), more frequently had lupus anticoagulant (6% versus 0.3%, p<0.001), anticardiolipin antibody (6% versus 0.9%, p<0.001), and pulmonary arterial hypertension (PAH) (52% versus 31%, p<0.001). SSc-SLE less frequently had calcinosis (13% versus 27%, p=0.007), telangiectasia (49% versus 75%, p<0.001) and diffuse subtype (12% versus 35%, p<0.001). There were no significant differences in the occurrence of renal crisis (7% versus 7%), interstitial lung disease (40% versus 34%), and digital ulcers (38% versus 32%). SSc-SLE had better survival (median 26.1 versus 22.4 years), but this was not statistically significant (log rank p=0.06). Female sex and diffuse subtype attenuated survival differences between groups (Hazard Ratio 0.70, 95% CI 0.45, 1.11). Conclusions: SSc-SLE are younger at diagnosis, more frequently have PAH, and less frequently have cutaneous manifestations of SSc. SSc-SLE patients should be monitored for pulmonary hypertension, interstitial lung disease, renal crisis and digital ulcers. Disclosure of Interest: None declared